Politics of precarity: neoliberal academia under austerity measures and authoritarian threat. (11th October 2019) - Loher, David; Strasser, Sabine
Abstract : In recent years, precarity has become the norm rather than an exception in contemporary European academia. This special issue on politics of precarity examines the economic, social and political crisis‐effects of the neoliberal turn in academia. It analyses how austerity measures and authoritarian politics have led to a proliferation of precarity among, mostly young, scholars. Politiques de précarité : le milieu universitaire néolibéral face aux mesures d'austérité et à la menace autoritaire: Au cours des dernières années, la précarité est devenue la norme plutôt que l'exception dans les universités européennes. Ce numéro spécial sur les politiques de précarité examine les effets économiques, sociales et politiques du tournant néolibéral sur le monde universitaire. Les analyses démontrent de quelles façons les mesures d'austérité et les politiques autoritaires résultent en une précarité élevée parmi les chercheurs – surtout les plus jeunes.